1992
DOI: 10.1111/j.1540-8159.1992.tb03081.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind Study of Submaximal Exercise Tolerance and Variation in Paced Rate in Atrial Synchronous Compared to Activity Sensor Modulated Ventricular Pacing

Abstract: To assess the variation in paced rate during everyday activity and the importance of atrioventricular synchronization (AV synchrony) for submaximal exercise tolerance, atrial synchronous (DDD) and activity rate modulated ventricular (VVI,R) pacing were compared in 17 patients with high degree AV block. The patients were randomly assigned to either mode and evaluated by treadmill exercise to moderate exertion and by 24-hour Holter monitoring after 2 months in the DDD and VVI,R modes, respectively. At the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…58,60,63 The treadmill test was equally used in studies with participants of younger and intermediate ages, and the bicycle ergometer was predominantly used in studies with individuals older than 65 years. The use of the bicycle or treadmill test was not associated with differences in 67 Sulke, 1991 74 Deharo, 1996 62 Mitsuoka, 1988 69 Kenny, 1986 65 Channon, 1994 60 Menozzi, 1990 68 Kamalvand, 1997 64 Jordaens, 1988 50 Hargreaves, 1995 63 Davis, 1985 61 Kristensson, 1985 66 Perrins, 1983 71 Avery, 1994 58 Yee, 1984 77 Saner, 1996 73 Capucci, 1993 59 Oldroyd, 1991 70 Rediker 67 Sulke, 1991 74 Hargreaves, 1995 63 Deharo, 1996 62 Menozzi, 1990 68 Saner, 1996 73 Oldroyd, 1991 65 Channon, 1994 60 Jordaens, 1988 50 Hargreaves, 1995 63 Avery, 1994 58 Rediker reporting benefits, and with both instruments a benefit was found for dual-chamber pacemakers. Conversely, studies that used the 6-minute walking test reported no additional benefit for dualchamber pacing.…”
Section: Exercise and Effort Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…58,60,63 The treadmill test was equally used in studies with participants of younger and intermediate ages, and the bicycle ergometer was predominantly used in studies with individuals older than 65 years. The use of the bicycle or treadmill test was not associated with differences in 67 Sulke, 1991 74 Deharo, 1996 62 Mitsuoka, 1988 69 Kenny, 1986 65 Channon, 1994 60 Menozzi, 1990 68 Kamalvand, 1997 64 Jordaens, 1988 50 Hargreaves, 1995 63 Davis, 1985 61 Kristensson, 1985 66 Perrins, 1983 71 Avery, 1994 58 Yee, 1984 77 Saner, 1996 73 Capucci, 1993 59 Oldroyd, 1991 70 Rediker 67 Sulke, 1991 74 Hargreaves, 1995 63 Deharo, 1996 62 Menozzi, 1990 68 Saner, 1996 73 Oldroyd, 1991 65 Channon, 1994 60 Jordaens, 1988 50 Hargreaves, 1995 63 Avery, 1994 58 Rediker reporting benefits, and with both instruments a benefit was found for dual-chamber pacemakers. Conversely, studies that used the 6-minute walking test reported no additional benefit for dualchamber pacing.…”
Section: Exercise and Effort Tolerancementioning
confidence: 99%
“…However, this conclusion is not robust, since there were several sources of heterogeneity. There were some 67 Sulke, 1991 74 Mitsuoka, 1988 69 Kamalvand, 1997 64 Davis, 1985 61 Kristensson, 1985 66 Perrins, 1983 71 Yee, 1984 77 Capucci, 1993 59 Oldroyd, 1991 70 Saner, 1996 73 Rediker, 1988 72 Sulke …”
Section: Exercise and Effort Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…1 Now, however, sensors are available that provide a means by which an adequate heart-rate response to exercise can be achieved without atrial sensing. 2 The results of several nonrandomized, observational studies of patients with pacemakers have suggested that physiologic pacing may reduce the risk of atrial fibrillation, stroke, and death. [3][4][5][6] A small, randomized study comparing physiologic (atrial) pacing with ventricular pacing in patients with sinus-node disease demonstrated a reduction in the risk of stroke, and extended follow-up showed a reduction in the rates of death and atrial fibrillation as well.…”
Section: Introductionmentioning
confidence: 99%
“…A special type of sinus node dysfunction is chronotropic incompetence, in which there is an inadequate sinus response to exercise or stress. Rate responsive pacemakers have been shown to benefit patients clinically by restoring physiological heart rate during physical activity 1, 29, 30 …”
Section: Indications For Cardiac Pacemaker Therapymentioning
confidence: 99%